The free-swimming planktonic copepoda - Sewell, R. B. Seymour (London, U.K. British Museum, 1971)
The John Murray Expedition 1933-34 Scientific reports; vol. 8 no.1
Keywords: Copepoda; Copepoda-John Murray Expediton-1933-1934.